2019
DOI: 10.32668/jkep.v4i1.231
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Metode Ceramah Dan Health Coaching Tentang Basic Life Support (Bls) Untuk Remaja Masjid

Abstract: Basic life support (basic life support) is an action when a patient is found to be suddenly immobile, unconscious, or not breathing, so check the patient's response. The purpose of this study was to determine the effectiveness of the lecture method and health coaching about BLS (Basic Life Support) in mosque youth. The research design is quasy-experiment. The population of this study was all male mosques in the year totaling 80 people. The sample in this study was simple random sampling. The research instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
3
0
4
Order By: Relevance
“…The results of the study conducted showed that there were differences in the frequency of hallucinatory signs and symptoms after being given nursing care. This result proves that the provision of nursing care routinely and continuously can provide a better direction (R. S. et al Aditya, 2019). Explains that proper management of people with schizophrenia will reduce positive symptoms (Rohmi, 2015).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The results of the study conducted showed that there were differences in the frequency of hallucinatory signs and symptoms after being given nursing care. This result proves that the provision of nursing care routinely and continuously can provide a better direction (R. S. et al Aditya, 2019). Explains that proper management of people with schizophrenia will reduce positive symptoms (Rohmi, 2015).…”
Section: Resultsmentioning
confidence: 82%
“…Hallucinations are a symptom of schizophrenia (Abdul Muhith, 2015). it was stated that 70% of schizophrenic clients had hallucinations (R. S. Aditya, 2019). Auditory hallucinations are generally defined as false perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa hipotesis telah dikemukakan seperti adanya kontak dekat dan penularan dari udara. Terdapat bukti bahwa tidak semua orang yang terinfeksi oleh kuman Mycobacterium leprae menderita kusta, iklim (cuaca panas dan lembab) diet, status gizi, status sosial ekonomi dan genetik juga ikut berperan (11), setelah melalui penelitian dan pengamatan pada kelompok penyakit kusta di keluarga tertentu. Belum diketahui pula mengapa dapat terjadi tipe kusta yang berbeda pada setiap individu dan faktor ketidakcukupan gizi juga diduga merupakan faktor penyebab.…”
Section: Patogenesis Kustaunclassified
“…rumah sakit yang mempengaruhi pengeluaran indvidu yang sakit. Kata Kunci : Rumah Sakit, Keputusan, Layanan Kesehatan PENDAHULUAN Rumah Sakit adalah salah satu fasilitas umum yang digunakan oleh masyarakat Indonesia dalam bidang kesehatan (Aditya, 2019b). Rumah sakit melakukan beberapa jenis pelayanan diantaranya pelayanan medik, pelayanan penunjang medik, pelayanan perawatan, pelayanan rehabilitasi, pencegahan dan peningkatan kesehatan, sebagai tempat pendidikan dan atau pelatihan medik dan para medik, sebagai tempat penelitian dan pengembangan ilmu dan teknologi bidang kesehatan serta untuk menghindari risiko dan gangguan kesehatan sebagaimana yang dimaksud, sehingga perlu adanya penyelenggaan kesehatan lingkungan rumah sakit sesuai dengan persyaratan kesehatan (Aditya et al, 2017…”
Section: Abstrakunclassified